Pipeline embolization device-assisted angioplasty for type II proatlantal intersegmental artery dissection inducing an embolic shower - Bao, Li; Pan, Zhenguo; Ji, Haifeng; He, Shuang (Frontiers in Neurology, 2025)
The proatlantal intersegmental artery (PIA) plays a crucial role in blood supply during embryonic development, and failure of its closure can lead to the persistent proatlantal intersegmental artery (PPIA), which may result in pathological changes such as dissection and aneurysms. We present a case of a patient with right type II PPIA dissection inducing an embolic shower, accompanied by left vertebral artery hypoplasia (VAH). Digital subtraction angiography (DSA) and high-resolution magnetic resonance vascular wall imaging (HRMR-VWI) showed the aneurysmal dilation of the false lumen in the right PPIA dissection and indicated the high risk of mural thrombosis and dislodgement. Following a comprehensive evaluation of the patient’s condition, we conducted pipeline embolization device (PED)-assisted angioplasty to treat the PPIA dissection and mitigate the risk of recurrent strokes. Postoperative follow-up indicated that the patient recovered smoothly, with no signs of recurrent stroke. This case highlights the critical need for prompt recognition and intervention in cases of rare vascular variants. The flow diverter implantation can greatly enhance patient outcomes and lower the risk of recurrent strokes, offering important insights for the clinical management of similar cases. Additional research is necessary to investigate the underlying pathological mechanisms of PPIA and its connection to stroke occurrence, which will help refine treatment strategies in the future.